ANALISIS CITRA MARKET PLACE PT TOKOPEDIA DALAM MENINGKATKAN KEPERCAYAAN KONSUMEN PASCA KEBOCORAN DATA PENGGUNA - Wildan IFauzi IHarahap; Aldi Raihan Ramadhan Daulay; Putri Nur Alfisyahri; Purnama Ramadani Silalahi (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2023)
The purpose of this study was to review the market place of PT Tokopedia in maintaining the image and trust of consumers after the leakage of customer data. The research method used in this study is a qualitative method, the data I use is in the form of writing I & I, not numbers. I have reviewed this data. Based on Ijournals, my mother, Iwebsite, and other official documents, PT Tokopedia informs about user data leaks. Tokopedia requires the necessary policies. Utilizing a new data security method, namely blockchain, as well as establishing special laws for the protection of personal data, is necessary to minimize the amount of business personal data. a significant impact on consumer confidence thereby influencing consumer purchasing power for sales made on the PT Tokopedia marketplace.